Analysis of the relationship between human complement components C3 & C4 deficiency and C– reactive protein levels as an indicator of the increase of microbial infections - Almabrouka, Muna; Abdallac , Ibrahim; Bumadiana, Mohamed; Agourib, Siham; Bozakouka, Ismaeel (Libyan Journal of Science &Technology, 2022)
The complement system is an important component of the immune system that consists of a group of plasma proteins produced by the liver and serving a defense function. As a result, the deficiency in any of the complement system components leads to the loss of the function of the deficient protein causing a specific clinical problem or disease. For that reason, this study was designed to investigate C3 and C4 deficiencies in young patients and to inspect the possibility of using C-Reactive Protein (CRP) test and the variation of C3 and C4 concentrations in children`s blood as an indicator of the onset of infection. This study was conducted in the children hospital in Benghazi city, Libya. The blood samples were collected from 446 children in all hospital units to examine the proportion of complement deficiency among those children and C3, C4 deficiency was set as an indicator of infection occurrence. The results of this study have shown a deficiency in complement proteins C3 and C4 were in 44 (10%) samples and 2 (0.4%) samples respectively, the female candidates had a higher rate of C3 and C4 deficiency than males. In addition, the CRP levels were elevated in 167 (55.9%) cases. Furthermore, the association between the increase of CRP levels and low levels of C3 and C4 was observed in 26 (8.7%) cases and 2 (0.6%) cases. These results suggest a strong association between complement proteins C3 and C4 deficiency and an elevation of CRP levels (P-Value=0.00), which supports the concept of using such association as an indicator of microbial infection